Effect of Benzyl-Adenine and Thidiazuron on In Vitro Multiplication of Ginger (Zingiber officinale Rosc.) Shoots - Endang Gati Lestari; Sitti Fatimah Syahid; Rossa Yunita; Tara Puri Ducha Rahmani; Imam Bagus Nugroho; Watson , Lee James (Journal of Tropical Biodiversity and Biotechnology, 2025)
The wilt disease caused by Ralstonia solanacearum and the leaf spot disease caused by Phyllosticta sp. are significant constraints in ginger cultivation as they can lead to crop failure. One approach to eliminating these diseases is to use disease-free ginger plantlets obtained through tissue culture propagation. This study investigated the influence of plant growth regulators, i.e., Benzyl Adenine (BA) and Thidiazuron (TDZ), on the in vitro multiplication of large white ginger shoots. The tested treatments included combinations of BA (0, 1, 2, 3 mg L-1) and TDZ (0, 0.1, and 0.2 mg L-1), with ten replicates each. A complete randomised factorial experimental design was employed. The observed variables were shoot height, number of shoots, number of leaves, and number and length of roots at 2, 4, 6, and 8 weeks of age. The results indicated an interaction between TDZ and BA for shoot number and root length. The highest numbers of shoots were obtained after eight weeks using 0.1 mg L-1 TDZ alone without BA. Meanwhile, the longest roots were obtained after eight weeks using a specific combination of TDZ and BA concentrations. Based on this study, we proposed a strategy to implement this protocol to induce the formation of shoots, leaves, and roots in a multistep tissue culture propagation.